Draft Annual Plan 2000-2001 Volume - II Government of Manipur - Planning Commission (Planning Commission, 2000)
G.N. Statement Draft Annual Plan(2000-2001) Draft Annual Plan 2000-2001- Proposal outlay Physical Targets and Achievements Annual Plan (2000-2001) Proposals for Spill over & Ongoing Programmes/Projects as in (Outlay/Expenditure) and Physical Targets/Benefits in relevant units of measurements Draft Annual! Plan 2000-2001 Proposals for Maximizing Benefits of completed programmes Projects (As on 31.3.2000) Draft Annual Plan 2000-2001 Proposals for Programmes/Projects New scheme (outlay/expenditure and physical targets/benefits in relevant unit of measurements) Summary statement Annual Plan 2000-2001 Proposal for Programmes/Projects Statement regarding Externally Aided Projects Annual Plan 2000-2001 Outlays By heads of Development for District Plan Centrally Sponsored Schemes.
Government of Manipur, Planning Department